ANALISIS EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN ACEH BESAR - wardani, raudhatun; Fadhlia, Wida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
Land taxes and rural and urban buildings (PBB P2) are among the most important local taxes that have the potential to increase local revenues. The purpose of this study is to determine the level of effectiveness of tax revenue earth and rural and urban buildings and how much contribution to the original revenue area in Aceh Besar District. The method of analysis used in this study is descriptive analysis method where by collecting data for the next descripted and processed. The results of this study indicate that the level of effectiveness of PBB revenues P2 in the Greater Aceh district increases every year with the same target setting every year. The contribution of PBB P2 to local own revenues has increased and decreased, by 2015 increasing by 2.21% from the previous year which was only 2.06% and categorized very less, in 2016 its contribution even decreased to 1.96% is still categorized very less. It is hoped that the government will do socialization by pairing banners notices that the SPPT has been issued and can be taken in a place that has been shown such as Keuchik office so that the public can see and be motivated to pay tax